Energy Efficiency Comparison of Common Packet Schedulers - Turyagyenda, C.; Albeiruti, N.; Zak, M.; Al-Begain, K. (IEEE., 2014)
This paper presents a characterisation of the energy performance of common and well-known packet schedulers in a multi-cell multi-user UTRAN long-term evolution (LTE) system. First, it was shown that the maximum SINR metric is more energy efficient than the round robin metric for both time and frequency domain packet scheduling. Second, it was shown that frequency domain packet scheduling had a greater impact on the energy efficiency of the system than time domain packet scheduling; i.e. RF Energy Reduction Gains (RF-ERG) ranging from 16% to 49% and 2% to 18% respectively.
Keywords: Energy Reduction Gains; Packet Scheduling; LTE